Dispensation for the candidates for permanent diaconate: Canon 1041, N. 3 (Roman replies and CLSA advisory opinions, 2007)
"Three cases were submitted to the Congregation for Divine Worship and the Discipline of the Sacraments asking for a dispensation from the impediment of previously attempting marriage for three candidates seeking ordination to the permanent diaconate. The three cases, and three responses are printed here, because although they are similar, they represent some different circumstances and responses. Also printed here is the follow-up letter from the Diocesan Bishop in 2006."